83 Virtual Intracavernosal Injection Training During the COVID Pandemic. Issue 1 (1st April 2022) - Zarowski, C; Higano, C; Wu, E; Sundar, M; Bentley, J; Flannigan, R
ABSTRACT: Introduction: Erectile dysfunction (ED) is a common side effect of prostate cancer treatment, and can cause considerable distress for the patient and partner. Therefore, it is beneficial to identify and implement interventions to help manage ED as early as possible. Intracavernosal injection therapy (ICI) is an option to treat ED but requires training patients to self-inject medication into the corpus of the penis. Due to the COVID-19 pandemic, the Sexual Rehabilitation Clinic (SRC) was closed resulting in delays in ICI training. In order to address this problem, we transitioned the training strategy from in-person visits to virtual care. Objective: This study describes our experience delivering ICI training virtually during the pandemic. Methods: Patients agreed to participate in the virtual training via web-based teleconference software and were assigned to read educational material and view an instructional video prior to the appointment, as per our in-patient clinic process. The virtual training sessions included review of anatomy, mechanisms of action of the medication(s), side effects, and management thereof. Preparation of the syringe and the process of injecting a prosthetic penis were demonstrated. Principles of medication titration were reviewed. Remaining questions were answered and virtual or telephone follow-up was scheduled. Results: Within 7 weeks of closure, we pivoted to offer our Sexual Health Clinic virtually. From July 2020 to May 2021, 50 patients had virtual appointments booked for ICI training, 49 of whom completed virtual ICI training (1 pt could not fill his prescription and didn't rebook). We learned early on that having proper visual props (medication vial, syringe, penis model and instruction booklet) and good camera positioning to clearly see the medication preparation and injection technique were instrumental for successful training. Virtual health appointments lasted 35 to 45 minutes compared to 60 minutes in-person, reducing training times by 15 to 25 minutes per patient. At the end of each session, participants verbally affirmed that the sessions were clear and easy to follow and that learning ICI from the comfort of home, without the stress of travel, and the cost of parking were beneficial aspects of virtual health. Another benefit from the clinic perspective was the elimination of clinic preparation pre-visit and post-visit cleaning. A post-session survey answered by 21 patients demonstrated that 80.9% were satisfied with the virtual teaching and that 52.3% were very confident or extremely confident about using ICI injections. 76% of respondents had used ICI within the last month at the time of the survey. Conclusions: The COVID-19 pandemic was an impetus for us to change our standard of practice for ICI training. Despite our concern that patients would not gain enough confidence if not seen in person, this was not the case. Benefits of virtual health included shorter clinic times, removal of geographic and financial barriers, and ability to provide timely training for ICI injections. Based on our positive experience delivering ICI training virtually, we plan to offer the option of in-person or virtual appointments when COVID-19 restrictions are lifted. Disclosure: No